Dust From the Solar System and Beyond - Alessandra Rotundi; Marco Fulle; Vincenzo Della Corte (© 2021 Elsevier Ltd. All rights reserved., 2021)
Dust is observed in almost all environments of the Solar System. Observing it by remote telescopes provides global information, but its exact nature remains undisclosed. Applying a sequence of laboratory analytical techniques on actual extraterrestrial samples provides a detailed understanding of dust's intrinsic nature, which depends on its formation and history. Extraterrestrial dust is routinely collected on Earth, by stratospheric balloon borne experiments, e.g. DUSTER, by stratospheric aircrafts, e.g. NASA Cosmic Dust Program, and from Antarctic ice samples, e.g. the Transantarctic Mountains collection. Samples from parent bodies, and interplanetary media can be collected and returned to Earth by space capsules, e.g. Stardust, Hayabusa, Osiris-Rex, Hayabusa2, or observed and characterized in situ by spacecraft, e.g. Rosetta (escorting and orbiting comet 67P/Churyumov-Gerasimenko) and Giotto (flying by comet 1P/Halley). Planetary dust retains signatures of processing, e.g. annealing, crystallization, hydration, which caused it to evolve from its primordial state. Analyzing dust in its present state leads to the reconstruction of its history from which we infer indications on Solar System formation and emergence of life. From dust's mineralogical and/or amorphous composition we can ascend to its parent body, when unidentified. Knowing the planetary body/environment from which it originates, dust provides clues about its parent body/environmental history. If dust is shown to originate from a mixture of solar system and interstellar sources its parent body can be classified as primordial, “frozen at the time of its birth”, providing clues on Solar System formation and possible hints on the origin of life on Earth. Thus, studying dust means following a path which brings us back to human and Solar System origins.